Forgotten dead: mob violence against Mexicans in the United States, 1848 - 1928 - Carrigan, William D. (Oxford Univ. Press, 2013)
Manifest Destiny and Mob Violence against Mexicans -- Judge Lynch on the Border -- Mexican Resistance to Mob Violence -- Diplomatic Protest and the Decline of Mob Violence -- Conclusion: Remembering the Forgotten Dead -- Appendix A: Confirmed Cases of Mob Violence against Persons of Mexican Origin and Descent in the United States, 1848-1928 -- Appendix B: Unconfirmed Cases of Mob Violence against Persons of Mexican Origin and Descent in the United States, 1848-1928